2018
DOI: 10.7150/ijms.27609
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Alterations in the Rat Testis after Methamphetamine Exposure

Abstract: Gamma-aminobutyric acid (GABA), GABA-A receptors and GABA transporter 1 (GAT1) were reported to be involved in the proliferation of Leydig cells, testosterone production and spermatogenesis. Since methamphetamine (METH) has been reported to have adverse effects on testis and its functions, the aim of this study was therefore to determine the changes of GABAergic activity in testis after METH exposure. Male Sprague-Dawley rats were divided into control, acute binge (AB-METH), escalating dose (ED METH) and escal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Regarding spermatogenesis, amphetamines induce apoptosis in murine testicular germ cells [114]. Oxidative stress, overproduction of serotonin and GABA, thermic rise, and decreased expression of progesterone and estradiol receptors in testis have been called into question in the pathogenesis of testicular damage [111,116,119].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding spermatogenesis, amphetamines induce apoptosis in murine testicular germ cells [114]. Oxidative stress, overproduction of serotonin and GABA, thermic rise, and decreased expression of progesterone and estradiol receptors in testis have been called into question in the pathogenesis of testicular damage [111,116,119].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in testicular GABA concentration has also been reported in methamphetamine treated rats [111]. Since GABA is involved in the proliferation of Leydig cells and testosterone production, Authors hypothesized that the increase in GABA concentration could represent a compensatory response to the detrimental effects of methamphetamine on Leydig cells [111].…”
Section: Effects On Testosterone Productionmentioning
confidence: 97%
See 2 more Smart Citations
“…To some extent, the exhaustion of energy and glucose metabolism might account for the aforementioned results. A recent study also showed that after METH exposure, the compensatory upregulation of gamma-aminobutyric acid (GABA), GABA-A receptors and GABA transporter 1 (GAT1) in rats testes tissues appeared [28], which might represent a homeostatic response to the adverse effects of METH exposure by inhibiting local mechanism and reducing energy consumption. Moreover, enzymes related to glycolysis, including HK1 and LDHC, might be broken down because of the reduction of GLUT1 and G-6-P according to the theoretical basis of enzyme catalysis [29].…”
Section: Discussionmentioning
confidence: 99%